Medical termination of pregnancy (Amendment Bill, 2021): Is it enough for Indian women regarding comprehensive abortion care?? - Sneha Kumari; Jugal Kishore (Wolters Kluwer Medknow Publications, 2021)
Medical termination of pregnancy (MTP) has been legalized in India since 1971 considering the huge burden of unsafe abortions. Even after about 50 years, Indian women continued to have unsafe abortions and face adverse and fatal consequences. At this point, only legislative amendments may not be sufficient but along with that, many other aspects need to be considered like awareness, availability, accessibility, affordability of quality MTP services, and contraceptives. People should know the adverse effects of taking unsupervised medical termination pills. Comprehensive abortion care should be provided at every level of health care to ensure the good reproductive health of the women.